Antibody-drug conjugates: beyond current approvals and potential future strategies - Siddharth Menon; Sagun Parakh; Andrew M. Scott; Hui K. Gan (Open Exploration Publishing Inc., 2022)
The recent approvals for antibody-drug conjugates (ADCs) in multiple malignancies in recent years have fuelled the ongoing development of this class of drugs. These novel agents combine the benefits of high specific targeting of oncogenic cell surface antigens with the additional cell kill from high potency cytotoxic payloads, thus achieving wider therapeutic windows. This review will summarise the clinical activity of ADCs in tumour types not covered elsewhere in this issue, such as gastrointestinal (GI) and genitourinary (GU) cancers and glioblastoma (GBM). In addition to the ongoing clinical testing of existing ADCs, there is substantial preclinical and early phase testing of newer ADCs or ADC incorporating strategies. This review will provide selected insights into such future development, focusing on the development of novel ADCs against new antigen targets in the tumour microenvironment (TME) and combination of ADCs with immuno-oncology (IO) agents.